Analysing the role of framework conditions influencing international entrepreneurial opportunity identification process (2017)
Objective:The objective of this paper is to determine and analyse the framework conditions that influence the entrepreneurial opportunity identification and action in the international market context. Research Design & Methods: Scholars from the International Business and International Entrepreneurship (IE) research fields agree that the process of internationalisation is triggered by opportunity identification. The extant literature is reviewed by assessing the framework conditions that domestic and international markets offer for entrepreneurial actions. An analytical juxtaposition of the influential factors is conducted in the light of various stages of the opportunity identification process by examining ? at each stage ? possible effects of domestic and international market context. Findings:This paper brings into the IE discussion a conceptual matrix of various elements and factors ? external conditions – which influence the creation of nexus by entrepreneurs to the markets. Implications & Recommendations:The conceptual matrix offers new insights for theoretical development and arguments for designing empirical research in terms of external conditions. It is expected to provoke more theoretical and practical questions from scholars within the IE field. Contribution & Value Added:The originality of this work lies in proposing a comprehensive framework to understand how context interacts with the entrepreneurial opportunity identification process.